SURFACE QUALITY AND CORROSION RESISTANCE OF 316L STAINLESS STEEL ELECTROPOLISHED USING PHOSPHORIC – SULFURIC ACIDS - Firmanto, Hudiyo; Arief, Budhyantoro (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
Electropolishing is an electrochemical surface finishing technique. It is commonly applied to equipment that requires a gleaming finish. This surface property is frequently required in 316L stainless steel (SS) medical implants. Electropolishing removes a thin layer from the metal's surface through electrochemical processes. This results in a very clean, smooth, and bright metal surface. The process parameters, such as electrolyte solution, electrical current, and electropolishing time, influence surface roughness and glossiness. The dissolution of metallic ions during the process may also affect the corrosion resistance of the treated material in addition to producing a shiny surface. This study investigated the surface glossiness, surface roughness, and corrosion of electropolished 316L SS. Electropolishing experiments on 316 SS were carried out using various H3PO4 (50%) and H2SO4 (32%) electrolyte solution compositions. The influences of electrolyte solution composition, electric current, and electropolishing time were studied. The results showed that increasing the H2SO4 content of the mixture and electropolishing the 316L SS for a longer period of time improved the surface roughness and glossiness. Under 10 Amp electric currents, the best surface glossiness was discovered. A corrosion test revealed that the electropolishing produced a Cr and Ni-rich layer that improved the corrosion resistance of the samples.